Atmospheric carbon removal via industrial biochar systems: A techno-economic-environmental study. (15th October 2022) - Fawzy, Samer; Osman, Ahmed I.; Mehta, Neha; Moran, Donal; Al-Muhtaseb, Ala'a H.; Rooney, David W.
Abstract: It is critical to develop carbon removal projects that are both effective and financially viable. Herein, we investigated the carbon removal potential of an industrial biochar system in Spain. This study is the first to assess the techno-economic-environmental impact of large-scale olive tree pruning residue pyrolysis for atmospheric carbon removal, using an integrated assessment framework that is based on current market dynamics. Production optimization using response surface methodology (RSM) was carried out, aiming to maximize yield, production throughput and stable carbon content while prioritizing stability. It was determined that optimized biochar production was attained at 650 °C and 15 min residence time. Furthermore, a biochar plant with a biomass processing capacity of 6.5 tonnes-per-hour was designed for further analysis. A thermodynamic model was developed using Advanced System for Process Engineering (ASPEN Plus) software, and the process was determined to be self-sufficient with the availability of surplus energy. Moreover, a life cycle assessment (cradle-to-grave) revealed that approximately 2.68 tCO2 e are permanently removed from the atmosphere per tonne of biochar produced, after accounting for the carbon footprint of the entire process. This corresponds to a carbon removal capacity of 3.26 tCO2 e per hour and the removal of approximately 24, 450 tCO2 e annually. The economic assessment revealed that the project is profitable; however, profitability is sensitive to pricing of the carbon removal service and biochar. A project internal rate of return (IRR) of 22.35% is achieved at a price combination of EUR 110/tonne CO2 e removal and EUR 350/tonne biochar, and a feedstock cost of 45 EUR/tonne (delivered with 20% moisture content), where service and product pricing are both within the lower bound of market pricing. If the project was exclusively designed to offer a carbon removal service, a minimum price of EUR 206/tonne CO2 e removal is required to achieve project profitability, based on the same feedstock cost. The findings of this study demonstrate the viability of immediately deploying large-scale biochar-based carbon removal via pyrolytic conversion of olive tree pruning residues to address the climate crisis. Graphical abstract: Image 1 Highlights: Optimized biochar production determined at 650 °C, 15 min residence time. Production process is self-sufficient with the availability of surplus energy. Life cycle assessment revealed that 2.68 tCO2 e are embodied per tonne of biochar. Carbon removal costs vary according to feedstock costs and project strategy. Profitability achieved at a price of EUR 110/tonne CO2 e and EUR 350/tonne biochar.